Comportamentos de saúde e bem-estar de adolescentes portugueses e estrangeiros residentes em Portugal em contexto de recessão económica - Matos, MG (2018)
This study aims to understand the evolution of health and risk behaviors of Portuguese and foreign teenagers living in Portugal between 2010 and 2014, a period that overlap with the economic recession. Participants are adolescents included in the study HBSC - Health Behaviour in School-aged Children in 2010 and 2014 in Portugal, including 11,079 young people from the 6th, 8th and 10th grades. Despite the general favorable evolution in health and wellbeing of adolescents, some vulnerabilities are identified, needing an urgent action. This study reinforces the importance of preventing the effects of the economic recession on health and adolescents behaviors, and points out some policy implications particularly in the area of education and health.